Outcome of the Community Service Program on Vegetable Consumption Education as a Strategy to Address Stunting Risk Groups in Coastal Areas - Bugis, Farida; Salakory, Melianus; Leuwol, Ferdinand Salomo (JENDELA PENGETAHUAN, 2024)
Stunting is a serious issue in developing countries like Indonesia, resulting from inadequate nutritional intake and impacting children's physical and cognitive growth. The 2022 Indonesian Health Survey recorded a stunting rate of 21.6%, with the highest prevalence found in East Nusa Tenggara (NTT), West Sulawesi, West Papua, and West Nusa Tenggara, while Bali had the lowest prevalence at around 8%. Stunting is not only a physical issue but also affects children's cognitive development, necessitating serious education and intervention. Coastal areas and small islands, including Osi Island in West Seram, are particularly vulnerable to this issue. The research was conducted using various data collection techniques such as questionnaires, interviews, observations, and documentation and was analyzed using descriptive qualitative methods. The findings indicate an increased community understanding of parasitic infections, greater awareness of environmental sanitation, changes in personal hygiene behaviour, and the use of local deworming medications. This increased knowledge forms the basis for prevention efforts, with a better understanding of parasitic infection causes, symptoms, and risks.